National Insurance Against Sickness and Unemployment : Full explanation of Mr Lloyd George's great scheme - Wilson, Philip Whitwell, 1875- (London : The Daily News)
1911 1911 1910s 4 pages 2 the scheme? Is he to lose all future benefit? The answer is, No. He may continue in the fund by joining the voluntary branch and paying 7d. a, week. His case will be a little like that of Mr. John Burns, who, as a workman, joined the Hearts of Oak, and as a Cabinet Minister keeps up his payments. The sickness and disablement scheme will thus include : By Compulsion — Men 9,200,000 Women 3,900,000 13,100,000 Boys 500,000 Girls 300,000 Total (compulsion) 13,900,000 Voluntary — Men 600,000 Women 200,000 Total (voluntary) ......... 800,000 Grand Total 14,700,000 The benefits are: (1).— MEDICAL RELIEF. The average payment at present for a friendly society doctor is 4s. per member per annum. This is not enough to enable a doctor to dispense the more costly drugs, and to treat the more difficult cases. Mr. Lloyd George proposes a really adequate payment for the friendly society doctor, who in future will do no dispensing. The drugs will be made up by the chemist, and whatever their cost they will be paid for separately by the fund. In future the doctor will prescribe without dispensing, and for the first time the poor will be assured of the costlier of necessary medicines. The only exception will be those remote country districts where there no chemist within reach. Here the doctor may still have to keep up a dispensary. (2).— A MATERNITY ALLOWANCE of £1 10s. will be paid on condition that the mother does not return to work for four weeks after child birth. This allowance will cost the fund 1 1/2 million a year. It will be paid not only to those mothers who, as wage earners, are within the fund, but also to those women who, as wives of members, do not earn wages, and, therefore, make no contributions. It will apply to illegitimate births as well as to legitimate, where, that is, the mother is a member. Here let me deal with the position of a girl who begins life either in a factory or in domestic service. She comes under the compulsory provisions, and pays her 3d. a week as long as she retains such employment. But suppose she marries and has to go out of the fund. How far does she lose future benefits? In the first place, she will probably marry a working man who is already in the fund. The household, therefore, benefits by whatever she may have paid in. Secondly, she will, without further payment, receive maternity benefit on every child-bearing. Thirdly, if she be left a widow, at whatever age, she can join the fund without paying up arrears, and at once become eligible for all benefits, just as if she had paid in money during the whole of her married life. There is no doubt that actuarially these are very favourable conditions. (3).— THE ATTACK ON CONSUMPTION, There are to-day 500,000 persons in these islands suffering from consumption. The available sanatoria only provide 2,000 beds. As a result the cost of proper treatment is usually quite prohibitive, and even where that cost is met the patient often has to wait for a vacancy until it is too late. Seventy-five thousand consumptives die every year, and during their illness they are not isolated, and so they spread the disease among those who are near and dear to them. Obviously it would enormously reduce the insurance fund if consumption could be stamped out. There will be, therefore, a loan of 13 million a year for the building of sanatoria for tuberculosis, and the co-operation of each locality will be expected as a condition for the assistance of the Treasury. There will also be a free grant of about a million a year for maintenance. This last grant is to be made at the rate of 1s. per annum per member, to be paid out of the Insurance Fund, with 4d. per member per annum added by the State. This does not mean that members will have to pay a shilling in addition to their weekly contributions, but that a sum equal to a shilling per member will be paid out of the general fund. (4).— SICK ALLOWANCES at the following rates: For men, 10s. a week for the first three months. For men 5s. a week for the next three months. For women, 7s. 6d. a week for the first three months. For women 5s. a week for the next three months. The lower rate for women is due to their lower scale of payment — 3d. instead of 4d. a week. The period of three months for maximum benefit is shorter, doubtless, than the present scale of certain friendly societies, but it must be remembered that consumption accounts for the great mass of longer illnesses, and consumption is specially treated. (5).— DISABLEMENT PENSION. For permanent inability to work, 5s. a week — the same figure, that is, as the old age pension now paid at the age of 70. This disablement pension will obviously be a colossal boon. Sickness benefit will not commence until the member has paid in for six months. Disablement pensions will not be payable until two years of membership have elapsed. These limitations are doubtless important at the outset of the scheme, when members will join for the first time at all ages. But in future years, when the scheme is steadily recruited from the ranks of children, the qualifying periods will be a mere formality. The disablement pension will, of course, cease at the age of seventy, when the old age pension commences. Certain modifications to benefits should be mentioned. At the beginning of the scheme persons of all ages up to 65 may join. The higher the age the more expensive will be the member, and for persons of advanced years a lower scale of benefits is, therefore, essential. Men over 50 years of age will receive 7s. 6d. for the first three months' illness, instead of 10s., and women over fifty years will receive 6s., instead of 7s. 6d. Next take the young members. Persons between 16 years and 21 years, if unmarried, will receive: Boys, 5s. for three months ; girls, 4s. for three months — this instead of the normal 10s. for three months. Such young persons would, as a rule, be living with their parents, and their illness ought not to be made a source of profit. Children under 16 years who, being employed for a wage, must join the fund, will be entitled to medical treatment only. Nothing is paid at death. What is popularly called life insurance, or funeral benefit, is left entirely to existing agencies. There is thus no competition between the Government scheme and great industrial assurance companies like the Prudential and the Pearl, or with the funeral policies of the friendly societies. This is a most important point for tens of thousands of insurance agents and for the holders of about 41 million death policies. Let us now consider the machinery of the scheme. Every insured person will have a card giving his name, of which card he will retain full possession. The card will tell nothing either as to his employer on the one hand or as to his friendly society on the other. Week by week he must present this card to his employer, who, when he pays the wages, at the same time affixes stamps to the value of 7d. for a workman, or stamps to the value of 6d. for a workwoman. After a certain period, when the card is filled, it will be returned 345/3/2/2